Ethnobotanical survey of plant species for herbal tea in a Yao autonomous county (Jianghua, China): results of a 2-year study of traditional medicinal markets on the Dragon Boat Festival - Bing Jin; Yujing Liu; Jiaxi Xie; Binsheng Luo; Chunlin Long (BMC, 2018)
Abstract Background Herbal tea is widely consumed in Jianghua, a Yao autonomous county in Hunan Province, China, to prevent and treat diseases. The materials in herbal tea at the traditional medicinal markets at the Dragon Boat Festival remain unknown. The aims of the paper were (1) to specifically investigate the materials of herbal tea used by Yao nationalities in Hunan Province, (2) to record the most common and the culturally important medicinal plant species in the markets, and (3) to compare the medical plant tradition both used for herbal tea between the Jianghua and Lingnan regions. Methods During 2016-2017, 215 vendors were interviewed at traditional medicinal markets at the Dragon Boat Festival in Jianghua to record plants used for herbal tea and to document traditional knowledge of their medicinal function, habitat, and conservation status. Bunches of medicinal plants were purchased to identify the species and to prepare voucher specimens. Cognitive salience (CS) based on free-lists and use value (UV) were calculated to analyze the cultural importance of medical plants; other quantitative methods (coefficient of similarity and chi-square analysis) were applied for comparison of herbal tea tradition between the Jianghua and Lingnan regions. Results A total of 169 species belonging to 66 families and 142 genera were recorded in herbal tea to treat health conditions in the study area. There were 30 health conditions that were recorded, with heat-clearing and detoxifying being the most common medicinal function, followed by treating rheumatism and promoting blood circulation. Of the 169 species, 97 were herbs. The whole plant was the most commonly used plant part in the preparation of herbal tea. According to the national evaluation criteria, three of these species are listed on "China's red list" and registered as vulnerable (VU). By comparing the coefficient of similarity of herbal tea plants and the number of mentions for part(s) used in Jianghua and Lingnan, the medicinal plant tradition is different in two areas. Conclusions Herbal tea in Jianghua reflects the cultural diversity of the Yao people and the plant diversity of the region. Future research on the safety, efficacy, and the adulterants of herbal tea are needed for sustainable utilization.